Trivulziana Cod. N. 1458: A new testimony of the “Landus- report” - Tóth, Gábor Mihály (Verbum – Analecta Neolatina, 2008)
The Trivulziana Cod. N. 1458 is a variant of the dispatch, known as the "Landus report" in the Hungarian historiography. This report narrates the history of Hungary from the death of Louis the Great up to the peace between Matthias Corvinus and Frederick III in 1463. However, the codex of the Trivulziana Library also contains a new closing section, which narrates the events following the death of Matthias. In this paper, I examine two questions: (a) was this closing section written by the same person as the so-called Landus report?; (b) does this closing section provide us new pieces of information concerning the history of Hungary? In addition to this, I give a general account of the content of the dispatch and review its editions and its manuscript tradition. Moreover, I outline its reception in the Hungarian historiography. Finally, in the Appendix I give the transcription of the closing section of the manuscript as well as another unpublished part of the manuscript, although the examination of this will be the subject of further studies.